Застосування математичних моделей і методів обчислення для дослідження динаміки рідини при обтіканні перешкод - Гета, Д. В. (ХНУРЕ, 2023)
This article presents a review of mathematical models and methods for numerical simulation of fluid dynamics when flowing around an obstacle, focusing on the study of various aspects of the problem, including the mathematical description of fluid motion, the choice of numerical methods for solving the equations, and the specifics of modeling the flow around obstacles. Approaches used in numerical models to account for the complexities of obstacle flowing are described, and applications of such modeling in various fields are discussed. In general, the article presents a review of modern mathematical models and methods used for modeling fluid dynamics when flowing around an obstacle and points out possible directions for further research in this area.
Keywords: динаміка рідини; обтікання перешкод; рівняння Нав'є-Стокса; чисельне моделювання